Behavioral and Psychological Symptoms of Dementia (BPSD): Clinical Characterization and Genetic Correlates in an Italian Alzheimer’s Disease Cohort - Scassellati, Catia (J Pers Med, 2020)
Background: The occurrence of Behavioral and Psychological Symptoms of Dementia (BPSD) in Alzheimer’s Disease (AD) patients hampers the clinical management and exacerbates the burden for caregivers. The definition of the clinical distribution of BPSD symptoms, and the extent to which symptoms are genetically determined, are still open to debate. Moreover, genetic factors that underline BPSD symptoms still need to be identified. Purpose. To characterize our Italian AD cohort according to specific BPSD symptoms as well as to endophenotypes. To evaluate the associations between the considered BPSD traits and COMT, MTHFR, and APOE genetic variants. Methods. AD patients (n = 362) underwent neuropsychological examination and genotyping. BPSD were assessed with the Neuropsychiatric Inventory scale. Results. APOE and MTHFR variants were significantly associated with specific single BPSD symptoms. Furthermore, “Psychosis” and “Hyperactivity” resulted in the most severe endophenotypes, with APOE and MTHFR implicated as both single risk factors and “genexgene” interactions. Conclusions. We strongly suggest the combined use of both BPSD single symptoms/endophenotypes and the “genexgene” interactions as valid strategies for expanding the knowledge about the BPSD aetiopathogenetic mechanisms.